Global food 50/50 report 2023/2024: Analysis of family-friendly workplace policies and gender equality in 51 global food system organizations - Global Health 50/50; International Food Policy Research Institute; UN Women; Tanaka, Sonja; Malapit, Hazel J.; Njuki, Jemimah (International Food Policy Research Institute, 2024)
The third annual Global Food 50/50 Report, a joint initiative of Global Health 50/50, the International Food Policy Research Institute, and UN Women, reviews the gender- and equity-related policies and practices of 51 global food system organizations to assess two interlinked dimensions of inequality: inequality of opportunity in careers within organizations and inequality in who benefits from the global food system. The Report highlights the progress, or lack thereof, made by food organizations in promoting diversity and equality in their leadership and decision-making. For the first time, the 2023/2024 Report expands its focus to address a policy area that plays a decisive role in promoting equality of opportunity in the workplace: the extent to which workplace policies recognize and support employees’ care responsibilities.